Who are the women wishing to opt for contraception? - Khudija Mushtaq; Mariam Ashraf; Inayat Hussain Thaver (Journal of the Pakistan Medical Association, 2020)
Abstract This descriptive cross-sectional research study was conducted to determine the characteristics of the women who intend to use a modern family planning method. For this 154 women were selected in a small village and face-to-face interviews were conducted. The findings indicate that 86 (56%) women intended to use a contraceptive method. The regression model indicates that women who had the knowledge about different methods, those who had previously ever used family planning method and those who had never used any traditional method are more likely to adopt modern contraceptive methods. Keywords: contraception, practices, family planning...